2009
DOI: 10.1097/rlu.0b013e31818f45ac
|View full text |Cite
|
Sign up to set email alerts
|

Value of Precise Localization of Recurrent Multiple Myeloma With F-18 FDG PET/CT

Abstract: A 37-year-old man with multiple myeloma in remission underwent routine fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) study for disease restaging. Both FDG-PET and CT images showed focal abnormalities in the region of the T6 vertebra, but the fused images that are routinely provided with PET/CT could precisely localize the FDG active lesion to a soft tissue focus in the epidural space, away from a lytic nonactive vertebral body lesion despite their close proximity. The PET/CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…18 F-FDG PET is useful for assessing the extent of active disease and treatment follow-up [2,4]. Cholewinski et al [5] reported a case of recurrent multiple myeloma diagnosed with 18 F-FDG PET. A previous report has shown that 11 C-choline PET was more sensitive than 18 F-FDG PET for detecting bone involvement [6].…”
Section: Introductionmentioning
confidence: 99%
“…18 F-FDG PET is useful for assessing the extent of active disease and treatment follow-up [2,4]. Cholewinski et al [5] reported a case of recurrent multiple myeloma diagnosed with 18 F-FDG PET. A previous report has shown that 11 C-choline PET was more sensitive than 18 F-FDG PET for detecting bone involvement [6].…”
Section: Introductionmentioning
confidence: 99%